2022
DOI: 10.9734/jeai/2022/v44i930863
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Potential of Three Plant Extracts in the Control of Some Major Fungi Associated with Cashew Seeds (Anacardium occidentale L.)

Abstract: Cashew (Anacardium occidentale L.), is an economically export oriented crop that could plays an important role in the Cameroonian economy. Owing to its importance, a study was carried out to evaluate the potential antifungal activities of three plants extracts against three major fungal pathogens associated to its seeds. To achieve this objective, cashew seeds samples were collected from Cameroon and Chad, and fungal pathogens isolated on Potato Dextrose Agar (PDA) culture medium. In vitro antifungal activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Explants on Petri dishes with 100% inhibition were transplanted onto extract-free PDA medium to demonstrate fungistatic or fungitoxic activity. The fungistatic activity observed with Allium ampeloprasum extracts are similar to that reported by [11] who showed that Erigeron floribundus and Euphorbia hirta extracts had fungistatic activity on the fungi associated with avocado. In addition, the results are also similar to those of [28], reported that Cupressus lusitanica extracts had fungistatic activity on the growth of Phytophtora colocasiae, the agent responsible for taro blight.…”
Section: Effect Of Plant Extracts On the Radial Growth Fungal Pathogenssupporting
confidence: 88%
See 3 more Smart Citations
“…Explants on Petri dishes with 100% inhibition were transplanted onto extract-free PDA medium to demonstrate fungistatic or fungitoxic activity. The fungistatic activity observed with Allium ampeloprasum extracts are similar to that reported by [11] who showed that Erigeron floribundus and Euphorbia hirta extracts had fungistatic activity on the fungi associated with avocado. In addition, the results are also similar to those of [28], reported that Cupressus lusitanica extracts had fungistatic activity on the growth of Phytophtora colocasiae, the agent responsible for taro blight.…”
Section: Effect Of Plant Extracts On the Radial Growth Fungal Pathogenssupporting
confidence: 88%
“…1 ml of each extracts at different concentrations were incorporated into 19 ml of PDA and poured into sterilised Petri dishes of 90 mm diameter and allowed to solidify in a fume hood which was lighted by flame from a Bunsen burner. After solidification, mycelia discs (5 mm) of 10-days old growing in pure cultures of each fungus were transferred to the Petri dishes with the help of a cork borer of 5 mm in diameter [11]. PDA plates mixed with fungicide (Dithane) at the recommended dosage of the producer (1 mg/ml) served as the positive control while distilled water served as the negative control.…”
Section: In Vitro Evaluation Of Antifungal Activities Of Plant Extrac...mentioning
confidence: 99%
See 2 more Smart Citations